2022
DOI: 10.1186/s13287-022-03052-2
|View full text |Cite
|
Sign up to set email alerts
|

ETV2 promotes osteogenic differentiation of human dental pulp stem cells through the ERK/MAPK and PI3K-Akt signaling pathways

Abstract: Background The repair of cranio-maxillofacial bone defects remains a formidable clinical challenge. The Ets variant 2 (ETV2) transcription factor, which belongs to the E26 transformation-specific (ETS) family, has been reported to play a key role in neovascularization. However, the role of ETV2 in the osteogenesis of human dental pulp stem cells (hDPSCs) remains unexplored. Methods Transgenic overexpression of ETV2 was achieved using a lentiviral v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…PI3K-AKT is an important intracellular pathway that can regulate cell survival, proliferation, protein synthesis, and other cell activities. The importance of PI3K-AKT pathway on osteogenesis has been proved by some studies ( 59 , 60 ), and the expression of PI3K and AKT protein was up-regulated under ES as proved by Western blot analysis ( Fig. 5L ).…”
Section: Resultsmentioning
confidence: 73%
“…PI3K-AKT is an important intracellular pathway that can regulate cell survival, proliferation, protein synthesis, and other cell activities. The importance of PI3K-AKT pathway on osteogenesis has been proved by some studies ( 59 , 60 ), and the expression of PI3K and AKT protein was up-regulated under ES as proved by Western blot analysis ( Fig. 5L ).…”
Section: Resultsmentioning
confidence: 73%
“…Simultaneously, we observed effective activation of the MAPK signaling pathway, which is also a classical pathway involved in bone formation. [ 68,69 ] This was manifested by a significant increase in the expression levels of phosphorylated ERK and JNK in the NT/CIN group compared to those in the PT group (Figure 6B,E, Supporting Information). In conclusion, these findings highlight the efficient promotion of osteogenic capability through NT/CIN surface modification and shed light on the potential cellular signaling pathways involving Wnt/Ī²ā€catenin and MAPK (Figure 6C).…”
Section: Resultsmentioning
confidence: 98%
“…Our previous research has established that ETV2 promotes ERK1/2 phosphorylation, which may facilitate the formation of the HIF-1Ī± and HIF-1Ī² heterodimer and translocate into the nucleus for transcriptional activity [ 15 , 28 ]. Through the separation of cytoplasmic and nucleoprotein, we observed that ETV2 substantially increased intracellular phosphorylated ERK1/2 (pERK1/2) and intranuclear HIF-1Ī± ( Fig.…”
Section: Resultsmentioning
confidence: 99%